JELINEK ET HANEKE. LA FEMME ÉVISCÉRÉE COMME OBJET DU REGARD - Noemina CÂMPEAN (Studia Universitatis Babeș-Bolyai. Philosophia)
Jelinek and Haneke. The Eviscerated Woman as the Object of Gaze. This paper aims to explore a psychoanalytical comparison between Erika from the novel The Piano Teacher (Die Klavierspielerin, 1983), and the same character from the Michael Haneke’s film, La Pianiste (2001), adapted after Elfriede Jelinek’s writing. Whereas the woman in the book can only exist as a mask in order to exist as a phallus (the version of the father, Fr. la Père-version) – according to Jelinek’s obsession with the monstrous couple eye-gaze, expressed in an unnatural sexuality –, the woman on the screen is caught between the instances of embedding (the woman as uterus – the mother, the woman as a living tomb – the daughter) and the demystification of sexuality which culminates in rape.